Supplementation of Vitamin D in Diabetic Patients - Rakesh Kumar Jha1 , Ankita Kondhalkar2 , Pradip Jain3 Mrs. Lata Kanyal Butola4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nearly 30 percent to 50 percent of people are estimated to have deficiency of vitamin D,and insufficiency and vitamin D deficiency are recognized as global health issues in the world. Althoughthe presence of hypo-vitamin D raises the risk of rickets and fractures, higher levels of vitamin D are alsoassociated with hypertension (HTN), cardiovascular disease (CVD) and cancer. In addition, the vitaminD levels are also associated with diabetes mellitus (DM) and chronic kidney disease (CKD). Deficiencyof vitamin D was linked to DM induction and progression. While the relationship between vitamin D andinsulin secretion, insulin tolerance, and ?-cell dysfunction is highlighted in patients with DM, evidence ofvitamin D and DM levels is inconsistent, and well-controlled studies are required.Aim: Supplementation of vitamin D in diabetic patients.Material and Method: The study included 50 patients were given vita D supplement and 50 subjects werenot given vita D supplement in diabetic people as the control group. Directly Observed Treatment in theDepartment of Clinical Biochemistry, Datta Meghe Medical College, SMHRC, Nagpur in collaboration withJNMC, ABVRH (Datta Meghe Institute of Medical Sciences Deemed To Be University), Sawangi, Wardha,Maharashtra.Conclusion: This study evaluated that vitamin D supplementation can improve HbA1c, insulin resistance,and insulin in short-term intervention in T1DM & T2DM patients, suggesting that vitamin D can beconsidered as a therapeutic agent along with the other T1DM & T2DM treatments. The findings show thatin non-additional diabetic patients, vit D concentration was substantially lower than the additional diabeticindividuals.